1998
DOI: 10.1097/00000433-199806000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Toward A Broader Definition of Heat-Related Death: Comparison of Mortality Estimates From Medical Examiners' Classification With Those From Total Death Differentials During the July 1995 Heat Wave in Chicago, Illinois

Abstract: The classification of heat-related deaths solely according to body temperatures underestimates the magnitude of heat-related mortality during heat waves. Broader classifications are often used, but their utility in defining the mortality and identifying at-risk populations has not been evaluated. Using death data from the July 1995 heat wave in Chicago, the authors compared heat-related mortality rates based on the classification of heat-related deaths by the Cook County Medical Examiner's Office (CCMEO), with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(29 citation statements)
references
References 10 publications
0
27
0
1
Order By: Relevance
“…Although some deaths may have merely been anticipated by a few days to weeks, Semenza et al (1999) estimated that only 26% of deaths were due to this type of displacement or "harvesting," leaving over 500 deaths directly attributable to the heat wave event. Even this number may be an underestimate, as Shen et al (1998) found that excess mortality rates during the Chicago heat wave were higher than the estimated heat-related mortality (24-26 per 100,000 as opposed to 19 per 100,000), likely due to an overly narrow classification of heat-related death.…”
Section: Mortality and Morbidity During The 1995 Chicago Heat Wavementioning
confidence: 92%
“…Although some deaths may have merely been anticipated by a few days to weeks, Semenza et al (1999) estimated that only 26% of deaths were due to this type of displacement or "harvesting," leaving over 500 deaths directly attributable to the heat wave event. Even this number may be an underestimate, as Shen et al (1998) found that excess mortality rates during the Chicago heat wave were higher than the estimated heat-related mortality (24-26 per 100,000 as opposed to 19 per 100,000), likely due to an overly narrow classification of heat-related death.…”
Section: Mortality and Morbidity During The 1995 Chicago Heat Wavementioning
confidence: 92%
“…However, the actual total is much higher since extreme heat results in increased mortality for many other causes of death, such as cardiovascular and respiratory disease (Shen et al 1998;Kilbourne 1997). The 1995 heat wave in Chicago was responsible for over 800 deaths alone, and estimates for the 2003 heat wave across Europe range from 22,000 to upwards of 50,000 deaths (Whitman et al 1997;WHO 2004;Brucker 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The resulting heat-related death count has been shown to be markedly smaller than the overall excess mortality observed during HW, particularly when the cause of death was not certified by specially trained physicians (Shen et al 1998). Excesses due to many causes of death other than heat-related causes (HRC) occur during HW.…”
Section: Introductionmentioning
confidence: 99%